Are we virtuously caring or just anxious?. (8th May 2023) - Kurth, Charlie
Abstract: According to Grossmann, the high levels of cooperation seen in humans are the result of a "virtuous caring cycle" on which the increased care that more fearful children receive brings increased cooperative tendencies in those children. But this proposal overlooks an equally well supported alternative on which children's anxiety – not a virtuous caring cycle – explains the cooperative tendencies of humans.